Utilização da torta de Neem (Azadirachta Indica) como antimicrobiano em rações de frangos de corte - Assunção, Patrícia da Silva (2016)
An experiment objective was conducted to evaluate the use of Neem cake (Azadirachta indica) as an antimicrobial in broiler rations. Used 240 chicks cutting males of Cobb, 1 day old, distributed in a completely randomized design with 4 treatments, 6 replications of 10 birds each. The treatments were basal diet without adding antimicrobial diet with 0.05% tylosin, diet with 0.05% Neem and diet with 0.1% Neem. The performance of the birds, weight gain, feed intake and feed conversion were evaluated at 7 and 21 days. There was also the analysis of digestibility of the feed nutrients, from 18 to 21 days of bird life. Swabs were performed in five birds each repetition to one, 14 and 21 days of age to Salmonella sp count. and Escherichia coli. At 21 days of age a bird by repetition was euthanized to make the collection and weighing of the lymphoid organs (spleen, bursa and thymus) of birds. Performance data and metabolization of the feed nutrients were subjected to analysis of variance (ANOVA) and the means were compared by Tukey test at 5% significance level. The E. coli count data were analyzed by the Kruskal-Wallis test. The use of Neem cake did not influence the performance variables evaluated, and also had no effect on digestibility. There was no growth of salmonella during the trial period, the means used. The Neem cake did not reduce the intestinal population of E. coli, and did not affect the weight of the lymphoid organs (spleen, bursa and Timo). We conclude that the use of Neem cake as a growth promoter and antimicrobial, did not affect the performance, digestibility and intestinal microbiota of birds up to 21 days old.